2018
DOI: 10.1186/s13014-018-0960-y
|View full text |Cite
|
Sign up to set email alerts
|

Additional radiotherapy following endoscopic submucosal dissection for T1a-MM/T1b-SM esophageal squamous cell carcinoma improves locoregional control

Abstract: Background: Endoscopic submucosal dissection (ESD) can be used as a less invasive treatment option for superficial esophageal cancer involving the muscularis mucosae (T1a-MM) or upper third of the submucosa (T1b-SM1). Additional treatment after ESD is needed to prevent lymph node metastasis. However, the efficacy of radiotherapy following ESD has not been well evaluated. Moreover, the clinical outcomes of patients with large mucosal defects of the esophagus who received radiotherapy after ESD have not been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…Analyses of resected specimens of pMM esophageal squamous cell carcinomas from patients who received surgical resection as first‐line treatment, including patients with vascular invasion, revealed concurrent lymph node metastasis in 0–26.7% of cases. In our summary of the main reports, concurrent lymph node metastasis occurred in 29 of 199 patients (14.6%, 95% CI: 10.0–20.3%) . A report of 50 patients with pMM cancer found that the incidence of lymph node metastasis was increased in patients with vascular invasion (invasion negative 4/38 (10.5%) vs. invasion positive patients: 5/12 (41.7%)) …”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 81%
See 3 more Smart Citations
“…Analyses of resected specimens of pMM esophageal squamous cell carcinomas from patients who received surgical resection as first‐line treatment, including patients with vascular invasion, revealed concurrent lymph node metastasis in 0–26.7% of cases. In our summary of the main reports, concurrent lymph node metastasis occurred in 29 of 199 patients (14.6%, 95% CI: 10.0–20.3%) . A report of 50 patients with pMM cancer found that the incidence of lymph node metastasis was increased in patients with vascular invasion (invasion negative 4/38 (10.5%) vs. invasion positive patients: 5/12 (41.7%)) …”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 81%
“…The metastasis rates for each group were 12/216 (5.6%, 95% CI: 2.9–9.5%) in the follow‐up observation group (six reports; Table ), 0/6 in the additional surgical resection group (three reports; 0%, 95% CI: 0–46.0%), and 1/17 in the additional chemoradiotherapy group (six reports; 5.9%, 95% CI: 0.2–28.7%) (Table ).…”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…First, we excluded patients who received additional treatment following ESD. Complementary chemoradiotherapy has been reported to lower the risk of nodal or distal metastasis associated with infiltrative tumors, 23,24 and patients could also benefit from ESD combined with additional treatment 25 . Second, ESD patients were strictly selected according to CT assessments.…”
Section: Discussionmentioning
confidence: 99%